The feasibility of modern technologies for reinforced concrete containment structures of nuclear power plants - Czerniewski, Sarah (Kansas State University, 2009)
This report explores the requirements for the design and analysis of concrete containment and shows how newer material technologies such as self-consolidating concrete (SCC) and fiber reinforcement could assist in the constructability and durability of new nuclear power plant facilities. SCC for example, enables concrete to flow in the forms around the reinforcement and provides a more uniform adhesion with the reinforcement. Additionally, fiber reinforcement in the concrete mix increases bonding capability, thus making the concrete less likely to fracture. In particular, the ease of constructability benefits offshore floating nuclear power plants and preapproved modular power plants. To differentiate, the offshore plant would employ the assembly line to make all the plants the same while the modular plant, designed to be used anywhere, is not site specific and is typically smaller. Regarding research method, the report starts with the history of the nuclear industry in the United States, including the last nuclear power plant constructed, clarifying that nuclear energy was first harnessed for a submarine propulsion system before being employed to generate electricity. After these early endeavors, two major accidents, Three Mile Island (March 28, 1979) and Chernobyl (April 26, 1986), provided information regarding the lack of safety of nuclear power plant design and operation. Since the containment building is the focus of this report, recognizing the loads and the load combinations for design was the next step in research. Following that, the next step was to determine the design considerations and analyze the containment structure. New material technologies clearly have opened the door to new construction techniques, and the combination of new materials and methods offers structural engineers opportunity to build inherently safer nuclear power plants.
Keywords: Nuclear power plant; Containment; Design loads; Reinforced concrete; Engineering, Civil (0543); Engineering, Nuclear (0552)